Effect of high-pressure treatment on the heat-induced emulsion gelation of rabbit myosin. (15th January 2022) - Bai, Yun; Zhang, Yulong; Cui, Xuhai; Deng, Shaolin; Gao, Tingxuan; Sun, Xiaomei; Zhou, Guanghong; Xu, Xinglian
Abstract: The effects of high-pressure treatment (100–200 MPa) on the emulsion and gelation properties of rabbit myosin were investigated. When the myosin treatment pressure was increased from 0.1 (control) to 150 MPa, the proportion of α-helix significantly decreased, those of β-sheet and β-turn significantly increased, and the absolute enthalpy value significantly increased ( P  < 0.05). Myosin emulsion exhibited increased storage modulus and loss modulus, increased gel strength, decreased centrifugal loss and a dense, compact network of emulsion gel when the myosin treatment pressure was increased from 0.1 to 150 MPa. When the treatment pressure was increased to 200 MPa, the emulsion showed decreased storage modulus and loss modulus, decreased gel strength, increased centrifugal loss, and a less compact network with large cavities and globular aggregates. Therefore, moderate pressure treatment (150 MPa) modified the myosin emulsion structure and improved the thermal, rheological and gelation properties of the myosin emulsion, while higher-pressure treatment (200 MPa) weakened the thermal, rheological and gelation properties of the emulsion. Highlights: High pressure (<150 MPa) significantly decreased the α-helix content and improved functional properties of myosin emulsion. High pressure (<150 MPa) improved enthalpy and transition temperature. High pressure (<150 MPa) can significantly improve the storage modulus and loss modulus of rabbit myosin emulsion. High pressure enhanced the network structure of emulsion gel.